Instructional Digital Leadership for Managing AI-Supported Interactive Learning Media in Schools - Refizuliana, Refizuliana; Lestari, Slamet (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed the landscape of educational technology, creating new opportunities for more adaptive, personalized, and interactive learning. Within this context, instructional digital leadership has become a critical factor in ensuring that AI-supported interactive learning media are effectively integrated into school practices to improve teaching and learning quality. This study aims to synthesize current evidence on how instructional digital leadership contributes to the management of AI-supported interactive learning media in schools. The study employed a Systematic Literature Review (SLR) approach by analyzing 21 Scopus-indexed journal articles published between 2018 and 2024 using the PRISMA framework. The findings reveal six interrelated dimensions of instructional digital leadership: technology vision and leadership, digital infrastructure management, teacher professional capacity development, AI-supported instructional supervision, data-driven decision-making, and strategic adaptation to digital innovation. These dimensions demonstrate that effective school leadership extends beyond administrative responsibilities by fostering technology-enabled pedagogical environments, supporting teachers' digital competence, and promoting sustainable instructional innovation. The review also identifies persistent challenges, including unequal digital infrastructure, varying levels of teachers' AI literacy, and organizational readiness for educational transformation. The study concludes that instructional digital leadership serves as a strategic foundation for establishing AI-responsive learning ecosystems in schools, where technological resources, pedagogical practices, and organizational leadership are aligned to enhance interactive learning and educational quality. These findings provide practical and conceptual implications for strengthening technology-integrated instructional leadership in contemporary education.